A política econômica do governo Lula: uma análise do I Plano de Aceleração do Crescimento - Garcia Junior, Nelson Calsavara (2017)
The main objective of this thesis was to analyze the Growth Acceleration Plan (PAC), in its first version (2007-2010), using as basis of information the reports made available on the program site. In this material were found several problems that prevented an evaluation, as the lack of macroeconomic data on the reflection of the program in the economy, the absence of a relation and the monitoring of all the works, the lack of identification of which were in charge of the public initiative and private, the deletion of justifications for both delays (and the judicialization, which did not appear in the reports and was also not mentioned in the thesis), as well as works that were not carried out, differences of concept between the management of the program and the Court (TCU), as well as the disagreement between the indicators prepared and the results presented, since the data provided by the government indicated that in the first version 82% of the predicted values were realized and in the second version, the result reached 99, 7%. In order to situate the program, the historical reconstruction of Lula's presidential mandates was chosen. In the first one, there was a mass occupation of party members in the ministries and the reversion of this situation, motivated by the formation of coalition presidentialism, as verified that ministerial reforms were necessary and the base of support was widened. The government had the right international scenario, favored domestic consumption, adopted targeted social policies, increased domestic debt and kept the exchange rate overvalued. In the second term, the political aspect was not addressed, on the understanding that coalition presidentialism had only been intensified. In addition, an expansionist economic policy prevailed, focused social policy and overvalued exchange rates, domestic consumption was favored, domestic debt increased, there was conviviality with deindustrialization and with an economic model different from that adopted by FHC, but favorable to the great capital